Monetary regimes: Is there a trade-off between consumption and employment variability? - Kent Matthews; David Meenagh; Patrick Minford; Bruce Webb (Cardiff University, Cardiff Business School, 2006)
Macro models generally assume away heterogeneous welfare in assessing policies. We investigate here within two aggregative models ó one with a representative agent, the other a long-used forecasting model of the UK ó whether allowing for dierences in welfare functions (speciÖcally between those in continuous employment and those with frequent unemployment spells) alters the rankings of monetary policies. We Önd that it does but that a set of policies (money supply targeting implemented by money supply control) can be found that are robust in the sense of avoiding very poor outcomes for either of the two groups.
Keywords: E52; E58; E61; 330; Robustness; heterogenous welfare; money supply rules; interest rate setting; price level targeting